Impact of patient, primary tumor and metastatic pattern including tumor location on survival in patients undergoing ablation or resection for colorectal liver metastases: A population-based national cohort study. Issue 2 (February 2021) - Scherman, Peter; Syk, Ingvar; Holmberg, Erik; Naredi, Peter; Rizell, Magnus
Abstract: Introduction: Selecting the optimal treatment strategy for patients with colorectal liver metastases (CRLM) aim to improve survival for the total cohort. Following the introduction of laparoscopic resections and ablation, localization may direct choice of method. The aim with this study was to re-evaluate prognostic factors that should be considered at the preoperative multidisciplinary tumor board, based on a national population cohort. Materials and methods: A national cohort with radically operated colorectal cancer in 2009-2013, also treated for CRLM was identified in Swedish national registries. Prognostic factors were identified and evaluated in multivariable analyses. Results: 1200 patients treated with resection and 125 with ablation only were included in the study cohort. Relative five-year survival was 54.7% (50.9%-58.4%) and 32.0% (22.4%-41.9%), respectively). High age, acute surgery and complications at time of primary tumor resection remained important risk factors at liver surgery, as well as the primary tumor characteristics; vascular invasion and high lymph node ratio. As for metastatic pattern; tumor size, location in segment 4, 6, 7 or 8, multiple metastatic sites and progress after preoperative chemotherapy were significant risk factors. In multivariate analyses, ablation therapy doubled the risk of death within 5 years. This strong negative impact was confirmed in a weighted propensity score analysis (HR = 2.1 (95 % CI 1.5 -3.0)) . Conclusion: Segmental localization and tumor size were prognostic factors but also patient and primary tumor factors significantly impacted survival after intervention for CRLM. Long-term survival was significantly lower after ablation therapy compared to surgical resection. Highlights: Primary tumor staging impact outcome after liver metastasectomy. Size of CRLM >20 mm increase the risk of death with more than 50%. Localization of CRLM impact survival negatively if involving segments 4, 6, 7 or 8. Ablation double the risk of death within 5 years in a propensity score analysis.